Morbidity and health seeking behavior among the rural Population, Malaysia - Maung, Theingi Maung; Deborah, Sherly; Narayanam, Harini; Fernandez, Kevin; Kumari, Usha (Asian Journal of Medical Sciences, 2020)
Background: Health seeking behavior is defined as any deed that an individual tackles to perceive themselves to have a health issue or to be sick for the endeavor of discovering a suitable countermeasure. Delays in seeking health care are usually associated with an increase in the mortality rate and the perk of early treatment and control are also acknowledged. Aims and Objective: The present study aimed at finding the morbidity and health seeking behavior among the rural population, Malaysia. Materials and Methods: A community survey was carried out in the rural area of Kedah State and the sample size was 114. A structured questionnaire was used and the data were collected by face to face interview method. Results: Majority of the residents (71.9%) were apparently healthy while 28.1% were diagnosed with illness. Top three common diseases were hypertension (53.1%), diabetes (34.4%) and heart disease (6.3%). About 81.3% of them were taking their medications regularly whereas18.7% were not compliant. Among those with illnesses,31.3% of the respondents were using traditional medicine. About half of the respondents felt that they need not get check-ups and this becomes the major barrier to health care. It was followed by long wait, lack of doctors and mass media. The source of health information was mainly from health staff followed by mass media, friends and campaigns. Conclusion: Based on the study we can conclude that improving health literacy through intensive awareness campaigns and mass media and providing access to technology may create more health awareness and health consciousness in individuals and encourage them to lead a healthy lifestyle. Increasing the number of health care professionals and health care centers will motivate the individuals to monitor their diseases and treatment to improve the quality of life.